2018
DOI: 10.1159/000495273
|View full text |Cite
|
Sign up to set email alerts
|

miR-1-3p Contributes to Cell Proliferation and Invasion by Targeting Glutaminase in Bladder Cancer Cells

Abstract: Background/Aims: Increasing evidence showed that miR-1-3p plays a major role in malignant tumor progression. However, the specific biological function of miR-1-3p in bladder cancer is yet unknown. Methods: The expression levels of miR-1-3p in bladder cancer tissues and cell lines were examined by qRT-PCR. Bisulfite sequencing PCR was used for DNA methylation analysis. The target of miR-1-3p was validated by a dual luciferase reporter assay, and the effects of miR-1-3p on phenotypic changes in bladder cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…It is worth mentioning that our results on GLS and GLS2 expression are in agreement with those of previous studies. For example, whereas the over-expression pattern of GLS was observed in breast, liver, and colon cancer [49,50,51,52], the under-expression pattern of this gene was noted in bladder and lung cancers [53,54]. In contrast, our results showed that GLS2 is over-expressed in bladder and lung cancers [55,56], whereas it is downregulated in liver cancer [57] which indicates that glutaminases are indeed differentially expressed in different types of human cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that our results on GLS and GLS2 expression are in agreement with those of previous studies. For example, whereas the over-expression pattern of GLS was observed in breast, liver, and colon cancer [49,50,51,52], the under-expression pattern of this gene was noted in bladder and lung cancers [53,54]. In contrast, our results showed that GLS2 is over-expressed in bladder and lung cancers [55,56], whereas it is downregulated in liver cancer [57] which indicates that glutaminases are indeed differentially expressed in different types of human cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, miRNAs have been presented to play an essential role in migration property of various cancer cells,13 as either EMT process regulators. microRNA-1-3p (miR-1-3p) was found as a novel marker and plays as a tumor growth and migration suppressor in urinary system tumors such as bladder cancer14 and prostate cancer 15. Previous preliminary reports showed that miR-1, a homologous analog of mir-1-3p, may reflect RCC heterogeneity 16.…”
Section: Introductionmentioning
confidence: 99%
“…Then, miRNA-mRNA regulatory network revealed that miR-1-3p, miR-10a-3p, miR-10a-5p and miR-133a-3p had rich external connections, while miR-99b-5p have few external connections. miR-1-3p acted as a tumor suppressor in acute myeloid leukemia [28], bladder cancer [29], non-small-cell lung cancer [30], hepatocellular carcinoma [31] and so on. Zhi Y et al reported that high miR-10a-5p expression was associated with poorer overall survival of AML patients [32].…”
Section: Discussionmentioning
confidence: 99%